Lipid attainment among patients newly treated with lipid-altering drugs. (September 2014) - Hess, Gregory; Chang, Chun-Lan; Chung, Karen
Abstract Objective: Guidelines for preventing and treating patients with coronary artery disease have traditionally focused on reducing low-density lipoprotein cholesterol (LDL-C). Current treatments are effective; however, previous studies have identified a significant proportion of patients that are not achieving the recommended lipid levels. New guidelines were introduced November 2013. The objective of this study was to examine recent practice patterns and factors related to initiating treatment for hypercholesterolemia, which provides a comparative baseline to the introduction of new guidelines. Research design and methods: We conducted a retrospective cohort analysis utilizing laboratory results of lipid profiles and medical claims from January 2007 to September 2011 to identify patients with elevated LDL-C and diagnoses of hypercholesterolemia without prior pharmacotherapy. Pharmacotherapy dispensed, treatment modifications, LDL-C-goal attainment, and potential drug intolerance were evaluated. Results: Overall, among newly treated patients, 70.9% achieved the recommended LDL-C level within the first year of treatment; however, only 19.4% of those with coronary heart disease (CHD) or CHD risk equivalents achieved the more aggressive LDL-C goal of <70 mg/dL (1.8 mmol/L). LDL-C goals were generally achieved with the use of statins; however, a majority of patients underwent treatment modification(s) (e.g., discontinuation or restart). More than half of the patients diagnosed with elevated LDL-C did not initiate pharmacotherapy. Limitations: Data was unavailable for inpatient hospitalizations, family history of cardiovascular diseases, body weight, and height, and likely under-reporting of smoking within claims data. Conclusions: Newly treated patients with elevated LDL-C results generally achieved the recommended and risk-specific LDL-C goal with the use of lipid-altering drugs; however, there still exists a notable population of patients with CHD or CHD risk equivalents who were not treated to goal and a significant number of patients who do not receive lipid-lowering pharmacotherapy. New therapies and prescribing practices are warranted to adequately address these two patient populations.